Mid to late holocene dry events in Colombia's super humid Western Cordillera reveal changes in regional atmospheric circulation. (1st June 2021) - Jaramillo, Daniel; Vélez, María I.; Escobar, Jaime; Pardo-Trujillo, Andres; Vallejo, Felipe; Villegas, Juan Camilo; Acevedo, Alba L.; Curtis, Jason; Rincón, Henry; Trejos-Tamayo, Raúl
Abstract: The Pacific coast of northern South America, from Panama to Ecuador, also known as the Chocó biogeographic region, is one of the wettest and more biodiverse places on Earth. These wet conditions are caused by the presence of a tropical low-level atmospheric current known as the Chocó low level Jet that transports moisture from the Pacific Ocean to the Andes of Colombia and is responsible for a large portion of moisture entering the continent, reaching as far as the Eastern Cordillera. In order to understand better the climate and ecosystem dynamics of such a wet region, we investigated the past hydroclimate and environmental conditions of a yet an unexplored area, the Medellincito wetland at 2020 m above sea level, located on the water divide of the Western Cordillera of Colombia, under the direct influence of the Chocó Jet. Our results indicate that between ∼6680 and 3710 cal yr BP the wetland had permanent waters and was surrounded by forest. This suggests wet conditions with a strong and persistent Chocó Jet. From ∼3710 to ∼1560 cal yr BP, the wetland dried out and open vegetation dominated by grasses replaced the forest. Later on, between ∼1200 and 750 cal yr BP the wetland formed again although with shallow waters, while open vegetation continued to expand. Humid conditions and the forest were re-established after 750 cal yr BP. We hypothesize that dry conditions in an otherwise very wet area were caused by the weakening of the Chocó Jet, possibly associated with ENSO-moderated changes in the temperature of the Pacific Ocean that coincided with changes in the position, relative to today's, of the Intertropical Convergence Zone. This record highlights that the ecosystems' dynamics in the Chocó biogeographic region are highly responsive to variations in moisture from the Chocó Jet, which in turn depends on temperatures in the Pacific Ocean. With current global change leading to the warming of the oceans, this highly biodiverse region can potentially be transformed into grass-rich ecosystems as it had occurred in the past. Highlights: Changes in humidity from one of the wettest places on Earth are inferred from diatom, lithological and geochemical records. Between between ∼3710 and ∼1560 cal yr BP, the Choco Jet was debilitated probably as a result of changes in the Pacific and Atlantic (ENSO and the relative position of the ITZC, respectively) causing dry conditions. The dry spell between ∼3710-1560 cal yr BP favoured the expansion of open vegeation and desiccated the wetland. This study suggests that the terrestrial and aquatic ecosystems of this region are highly sensitive to variations in global climate via changes in the intensity of the Choco Jet.